PERLINDUNGAN HUKUM MEREK ASING TERKENAL TERHADAP PRAKTEK PEMALSUAN MEREK DI INDONESIA (Studi Kasus Merek Kinotakara: Putusan No. 015/PK/N/HAKI/2005) - , DIEGO ARIZONA, Prof. M. Hawin, S.H., L.L.M., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to determine the various forms of legal protection famous foreign brands that given by Act in Indonesia (especially Act No.15 Year 2001 about trade mark). In addition, to analyze the law judgment in the case of foreign brand \"KINOTAKARA\" counterfeit, that announced it could not to be categorized as a famous brand is right or not. The research is working with library materials that were secondary material, and then it was called library research. It is started by documents research to learn, examine, and research the law materials, like literature books, papers, articles, research results, theses, Acts of Trade Mark, ratified International Treaties, jurisdiction, and Minister's rules. And the last, to find law-shields for famous foreign brand against the counterfeit in Indonesia (\"KINOTAKARA\" brand case studies). The arrangement of protection about famous foreign brands could be categorized into two types according to UUM 15/2001. First, preventive protection that written on Section 6 subsection (1) letter b and subsection (2) UUM 15/2001. Second, repressive protection that written on Section 37 subsection (2) and Section 68 subsection (1). Furthermore, the consideration of the judges indirect announced that âKINOTAKARAâ brand owned by K-LINK is not a famous brand was inexact. According to the evidences, facts, and testimonies told that KINOTAKARA brand owned by K-LINK met the famous brand requirements, according to Section 6 subsection (1) letter b UUM 15/2001. Moreover, PT Royal Body Care had a negative will in registries âKINOTAKARAâ brand in Indonesia.